2010
DOI: 10.3390/molecules15042398
|View full text |Cite
|
Sign up to set email alerts
|

Pellitorine, a Potential Anti-Cancer Lead Compound against HL60 and MCT-7 Cell Lines and Microbial Transformation of Piperine from Piper Nigrum

Abstract: Pellitorine (1), which was isolated from the roots of Piper nigrum, showed strong cytotoxic activities against HL60 and MCT-7 cell lines. Microbial transformation of piperine (2) gave a new compound 5-[3,4-(methylenedioxy)phenyl]-pent-2-ene piperidine (3). Two other alkaloids were also found from Piper nigrum. They are (E)-1-[3’,4’-(methylenedioxy)cinnamoyl]piperidine (4) and 2,4-tetradecadienoic acid isobutyl amide (5). These compounds were isolated using chromatographic methods and their structures were eluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 7 publications
2
37
0
1
Order By: Relevance
“…33a, 101a (Tackie et al 1975) P. hancei Maxim. 101a, 117a (Narui et al 1995) P. longum L. 1a, 11a, 13b b , 16a, 33a, 36ab, 37 b , 39b, 46a, 47ab, 50b, 51a, 53b, 84a, 101ab (Dhar and Atal 1967;Koul et al 1988;Sun et al 2007;Li et al 2013) P. nigrum L. 8b, 13abk, 14abk, 16a, 33a, 34a, 37abkp, 38abk, 41k, 51a, 62ak, 89b, 99ab, 100a, 101abk, 103b, 112a, pipercycliamide (Wei et al 2004;Siddiqui et al 2004;Ee et al 2010;Dawid et al 2012) P. novae-hollandiae Miq. 101a, 112a (Loder et al 1969) P. peepuloides Roxb.…”
Section: Phytochem Revmentioning
confidence: 96%
“…33a, 101a (Tackie et al 1975) P. hancei Maxim. 101a, 117a (Narui et al 1995) P. longum L. 1a, 11a, 13b b , 16a, 33a, 36ab, 37 b , 39b, 46a, 47ab, 50b, 51a, 53b, 84a, 101ab (Dhar and Atal 1967;Koul et al 1988;Sun et al 2007;Li et al 2013) P. nigrum L. 8b, 13abk, 14abk, 16a, 33a, 34a, 37abkp, 38abk, 41k, 51a, 62ak, 89b, 99ab, 100a, 101abk, 103b, 112a, pipercycliamide (Wei et al 2004;Siddiqui et al 2004;Ee et al 2010;Dawid et al 2012) P. novae-hollandiae Miq. 101a, 112a (Loder et al 1969) P. peepuloides Roxb.…”
Section: Phytochem Revmentioning
confidence: 96%
“…The compound 37 showed inhibition of sICAM1/LFA1 interaction‐mediated human THP1 cell adhesion at IC 50 25.0 μg/ml after 1 hr by The enzyme‐linked immunosorbent assay (ELISA) (Matsuda et al, ). A study performed by Ee, Lim, Rahmani, Shaari, and Bong () found that 37 is extremely cytotoxic (IC 50 13.0 μg/ml) against the HL60 (human promyelocytic leukemia cells) cell line. It, however, showed a much lower potential (IC 50 1.8 μg/ml) against the MCF‐7 (breast cancer) cell line.…”
Section: The Chemistry and Pharmacology Of Artemisia Alkaloids/alliedmentioning
confidence: 99%
“…It, however, showed a much lower potential (IC 50 1.8 μg/ml) against the MCF‐7 (breast cancer) cell line. The compound 37 after an extensive investigation has been established as a potential anticancer hit and subjected to further optimization (Ee et al, ). Likewise, the compound 37 (n‐isobutyldeca‐trans‐2‐trans‐4‐dienamide) has been approved as a flavoring agent or adjuvant by FDA (The Joint Expert Committee on Food Additives Flavor No.…”
Section: The Chemistry and Pharmacology Of Artemisia Alkaloids/alliedmentioning
confidence: 99%
“…The amide group and the aliphatic chain could be the key domain for the insecticidal activities of the compounds, while the methylenedioxy phenyl unit might be a synergistic group. Several isobutyl-type amides weakly inhibited cell proliferation of breast cancer (MCT-7) and human leukemia (HL-60) cell lines and displayed major apoptosis-inducing effects [27,28]. Among them, the isopentyl amides possessed more biological diversities than that of amides only bearing a long chain.…”
Section: Isobutyl-typementioning
confidence: 99%